Insulin resistance and geographical origin: major predictors of liver fibrosis and response to peginterferon and ribavirin in HCV-4. Issue 12 (10th August 2009) - Moucari, R; Ripault, M-P; Martinot-Peignoux, M; Voitot, H; Cardoso, A-C; Stern, C; Boyer, N; Maylin, S; Nicolas-Chanoine, M-H; Vidaud, M; Valla, D; Bedossa, P; et al.
Abstract : Background and aims: Hepatitis C virus (HCV) genotype 4 (HCV-4) is increasing in prevalence in Western countries. However, little is known about the severity of the disease and response to treatment. The aim of this study was to assess the predictors (logistic regression) of severe fibrosis (METAVIR score F3–F4), and sustained virological response (SVR) to peginterferon and ribavirin in 226 consecutive HCV-4 patients (Egyptians 40%, Europeans 35% and Africans 24%). Patients and methods: Insulin resistance was assessed using the homeostasis model (HOMA-IR). Serum HCV-RNA level (bDNA) and subtypes of HCV (LiPA) were determined for all patients. Results: Insulin resistance (HOMA-IR >3) was present in 105 patients (46%), and was associated with: age >45 years (OR, 2.614; 95% CI, 1.316 to 5.194), body mass index (BMI) >25 kg/m 2 (OR, 2.105; 95% CI, 1.048 to 4.229), serum HCV-RNA >800 000 IU/ml (OR, 3.143; 95% CI, 1.503 to 6.574), severe fibrosis (OR, 2.657; 95% CI, 1.214 to 5.818), and steatosis >30% (OR, 2.488; 95% CI, 1.105 to 5.602). Severe fibrosis was present in 67 patients (29%) and was associated with Egyptian origin (OR, 5.872; 95% CI, 2.747 to 12.553), excessive alcohol intake (OR, 5.311; 95% CI, 1.287 to 21.924), and HOMA-IR >3 (OR, 3.864; 95% CI, 1.859 to 8.034). 108 patients received a 48 week course of peginterferon plus ribavirin. SVR (undetectable serum HCV-RNA (TMA) 24 weeks after treatment stopping) was achieved in 59 patients (55%) and was associated with Egyptian origin (OR, 13.119; 95% CI, 3.089 to 55.706), HOMA-IR <2 (OR, 5.314; 95% CI, 1.953 to 14.459), and non-severe fibrosis (OR, 8.059; 95% CI, 2.512 to 25.855). Conclusion: Insulin resistance and geographical origin are major predictors of liver fibrosis and response to peginterferon and ribavirin in HCV-4 patients. Insulin resistance is frequently encountered in these patients, and correlated independently with serum HCV-RNA.